Ecology of smooth-coated otter (Lutrogale Perspici/Lata) in the lower Kinabatangan Wildlife Sanctuary, Sabah, Malaysia - Leona Wai (2019)
Despite increasing levels of habitat loss and disturbance, and conversion of natural forest habitats to agricultural plantations in wetland areas in Borneo, very little is known about the Bornean otter species within these threatened wetland habitats in the island of Borneo. The aim of the present study was to gather baseline data on the population and habitat relations of otters and identify management issues affecting otter survival in the wild, which in turn may be useful for monitoring and managing this species with a view to conserve them. Set mainly in the lower reaches of the Kinabatangan River floodplain in Sabah, Malaysia, this study sought to (1) determine the presence and absence of otter species, including mapping their distribution across different habitat structures in the secondary lowland fragmented forest along the Kinabatangan River; (2) investigate the activity pattern of Kinabatangan's otters; and (3) discern local villager's perceptions towards otters, specifically to identify human-otter conflict. In addition to direct sightings, the presence of otters within an area is also strongly associated with the presence of their holts, spraints, grooming sites and footprint tracks; therefore, indirect observation techniques i.e., based on otter sign survey were used to detect the presence of otters in this study. A total of 25 sites were surveyed over a 12-month period. Each site was spaced in 1km intervals along the 40 km study area of the Kinabatangan River. Overall, 80 otter signs were detected and all belonged to the smooth-coated otter, Lutrogale perspicillata. Based on GLM result, presence of otter is positively correlated with high percentage of bare ground cover, sparse ground vegetation, steep riverbank slope, areas near to oxbow lakes, tributaries and human settlement, as well as grassland areas. However, based on occupancy modelling, otter occupied areas with sparse canopy cover and dense ground vegetation. The contrast in the GLM and occupancy result shows that there was a false absence occurred during the sampling. Areas with close proximity to oxbow lakes has the highest detection of otter sign, while areas with dense vegetation cover has the lowest detection. Four camera traps were deployed in front of two fresh otter halts for 15 non-consecutive months. The result showed that the Kinabatangan's otter mostly active during early morning and late evening, which was influenced by prey abundance and visibility, ambient temperature and human disturbances. A total of 58 respondents were interviewed in Batu Puteh village, Kinabatangan and most of the respondents (56.9%) were fishermen. Based on the interviews, 57% of the respondents held positive perceptions of otters and the level of human-otter conflict was relatively low in Batu Puteh village. The results of this study will be important in determining the current conservation status of Bornean otters in the lower Kinabatangan and provide a valuable baseline to assist in future population monitoring efforts.